2009
DOI: 10.1038/nrg2522
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome positioning and gene regulation: advances through genomics

Abstract: Knowing the precise locations of nucleosomes in a genome is key to understanding how genes are regulated. Recent ‘next generation’ ChIP–chip and ChIP–Seq technologies have accelerated our understanding of the basic principles of chromatin organization. Here we discuss what high-resolution genome-wide maps of nucleosome positions have taught us about how nucleosome positioning demarcates promoter regions and transcriptional start sites, and how the composition and structure of promoter nucleosomes facilitate or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
895
1
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 947 publications
(956 citation statements)
references
References 131 publications
(184 reference statements)
54
895
1
6
Order By: Relevance
“…It has been reported that nucleosomes acquire an open chromatin structure following the binding of transcription factors ). To analyze the nucleosome structure, Nucleosome-Seq (Albert et al 2007;Jiang and Pugh 2009;Schones et al 2008) was used in DLD-1 and TIG-3 cells. We generated a total of 130,088,634 36-bp sequence tags from micrococcal nuclease-digested genomic DNA and calculated the occupancy of the nucleosome according to a previously reported procedure (Albert et al 2007) (Supplementary Fig.…”
Section: Epigenetic Regulation In Regions Surrounding Hif-1a Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that nucleosomes acquire an open chromatin structure following the binding of transcription factors ). To analyze the nucleosome structure, Nucleosome-Seq (Albert et al 2007;Jiang and Pugh 2009;Schones et al 2008) was used in DLD-1 and TIG-3 cells. We generated a total of 130,088,634 36-bp sequence tags from micrococcal nuclease-digested genomic DNA and calculated the occupancy of the nucleosome according to a previously reported procedure (Albert et al 2007) (Supplementary Fig.…”
Section: Epigenetic Regulation In Regions Surrounding Hif-1a Bindingmentioning
confidence: 99%
“…Furthermore, we carried out Illumina GA sequencing analysis using micrococcal nuclease-digested genomic DNA (Nucleosome-Seq) (Albert et al 2007;Jiang and Pugh 2009;Schones et al 2008). We examined the changes in nucleosome structure caused by HIF-1a binding and the subsequent transcriptional activation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several mechanisms that prevent spreading may trivially solve the problem of restoring the parental modification pattern when exact boundaries are important. Examples include nucleosome-depleted regions (see, for example, Jiang and Pugh, 2009;Mavrich et al, 2008;Yadon et al, 2010), bound proteins (e.g., CTCF) or histone variants (e.g., H2A.Z) in the vicinity of positions that border the different chromatin domains, or the marking with a particular histone modification directly after replication due to other signalling factors.…”
Section: Discussionmentioning
confidence: 99%
“…These processes control cell fate through regulating gene and miRNA expression, as well as through parental imprinting, X chromosome inactivation, suppressing of transposons, and regulating developmental processes [4,6]. The epigenome provides the flexibility to address a changing environment above the rather rigid architecture of DNA sequence information and thus greatly affects the development and formation of a phenotype with no alteration in the genotype.…”
Section: What Is Epigenetics?mentioning
confidence: 99%